Konsep Dasar Hukum Waris di Indonesia dalam Perspektif Sejarah. - Yusrolana (Asy-Syari’ah : Jurnal Hukum Islam, 2015)
The basic concept of inheritance law in Indonesia something grounded and must be understood by all the people of Indonesia as a system that will be handed down for generations Indonesia who will run the existence of inheritance law in this country, history will prove that the existence of laws of inheritance are shared by most of the people Indonesia is a standard rule of Islamic law is the Qur’an, in the Koran provisions relating to Mawaris already outlined the development of the law does not deny the inheritance from Indonesia before independence and after Indonesian independence. In carrying out the Inheritance Law no legal basics about heir, is concerned with laws that define the legal position of a person who dies, he is entitled to the full to bequeath their wealth to anyone through a will and testament will apply when a person is already dead but when someone is not dead it will still be changed, otherwise if it dies it will have legal ketepan existence that can not be changed even if there are people who the rightful heir, and the provision of an heir by a will does not mean to abolish the right to inherit it ab intestato.